PENGARUH PENERAPAN PERENCANAAN PAJAK (TAX PLANNING) PAJAK PENGHASILAN PASAL 21 TERHADAP PPH BADAN (STUDI KASUS PT. TIARA INSANI PERSADA) - Selvy Irwanti Ramadhani; Parso Parso; Helena Louise Panggabean (Institut Teknologi dan Bisnis Swadharma, 2022)
The purpose of this study is to determine the application of tax planning PPh Article 21 at PT Tiara Insani Persada and its impact on the paid Corporate Income Tax. This research is qualitatively carried out by analyzing the calculation of employee taxes using three methods and adjusting to the current regulations. The data is processed by a descriptive analysis test, namely by collecting and clarifying existing data. Then analyze the data to provide an accurate picture of the state of the company. The research results are that PT Tiara Insani Persada has not implemented tax planning according to applicable regulations so the corporate income tax rate that must be paid becomes very large. After-tax planning following applicable regulations, PT Tiara Insani Persada managed to save the tax burden it owed